Amathus During the First Iron Age - Aupert, Pierre 1941- (1997)
Amathus appears as a true city in Cypro-Geometric IB, at the dawn of the Iron Age, but its origins may date from the beginning of the 11th century B. C. Its prosperity in the Iron Age may be due, at least in part, to its location, which allowed it to control the Kalavassos mines. Its religion blended scarcely Hellenized Cypriot tradition with Syro-Palestinian tradition. From the Cypro-Geometric IB period on, the tombs contain many Phoenician, and later Euboean, imports attesting to increasing foreign relations. A Phoenician necropolis confirms the presence of a sizable Phoenician colony. At the end of the Cypro-Geometric and in the Cypro-Archaic period, goldsmith shops produced remarkably cosmopolitan work. The existence of a Near Eastern type royalty, shown by recent excavations of the palace, reflects these influences. Despite the Greek names of the earliest kings, the politics of the kingdom was almost constantly pro-Persian, so the Archaic period saw greatly improved economic life, exemplified by the local goldsmith industry and rich deposits of local and imported ceramics.